ANALISIS DETERMINAN KUALITAS INFORMASI LAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN SISTEM PENGENDALIAN INTERNAL SEBAGAI VARIABEL MODERASI - Papat Adhitama , Panji; Suratno; Supriyadi, Edy (SEKOLAH PASCASARJANA PRESS, 2019)
This study aims to determine the factors that influence quality of information on local government financial reports in the Depok City Government with an internal control system as a moderating variable. These factors include Competence of Human Resources, Regional Financial Management Information Systems and Government Accounting Standards. Type of research is quantitative research using primary data. Data collection techniques are questionnaires. Population and samples in this study are Head of Finance Subdivision, Expenditure Treasurer and financial staff and accounting compilers of financial statements as respondents, amounting to 114 of the 38 SKPDs of Depok City Government. Data were analyzed using Moderated Regression Analysis with SPSS Statistics 22 software. The results showed that partially the Competence of Human Resources, Regional Financial Management Information Systems and Government Accounting Standards had a significant positive effect on the Quality of Information on Local Government Financial Reports. While the Internal Control System cannot moderate the influence between Human Resource Competencies, Regional Financial Management Information Systems and Government Accounting Standards with the Quality of Information on Local Government Financial Reports.